Occurrence of Marek`s Disease in Vaccinated Poultry Flocks of Haryana (India) - Kamaldeep; Sharma, P.C.; Jindal, N.; Narang, G. (International Journal of Poultry Science, 2007)
Marek`s Disease (MD), which is a lymphoproliferative disease of chickens, remains one of the most important diseases. In the present study, occurrence of Marek`s disease virus in ten vaccinated poultry flocks of Haryana (India) from different geographical locations was determined on the basis of clinical signs, gross and histopathology and precipitation test. The vaccines used were either HVT alone or in combination with SB-1. Samples from all the flocks had gross and histopathological lesions suggestive of Marek`s disease. Grossly, visceral tumors in liver, spleen, kidney and ovary were observed. The characteristic histopathological lesions included infiltration of pleomorphic lymphoid cells such as lymphoblasts, small and large lymphocytes, plasma cells and occasionally MD cells in different organs. The lesions were non-capsulated and infiltrative type. In immunodiffusion test, feather follicle tip samples from five flocks gave a positive precipitation reaction.